Policy content and stakeholder network analysis for infant and young child feeding in Nepal - Sumit Karn; Madhu Dixit Devkota; Shahadat Uddin; Anne Marie Thow (BMC, 2017)
Abstract Background Despite concerted effort from government and partners, Nepal continues to have a high burden of under nutrition among children. Identifying opportunities to strengthen policy support for infant and young child feeding (IYCF) is a key component to improve child survival, growth and development. This study aims to explore policy support for IYCF and to identify the influential stakeholders for IYCF for effective future policy development and programmatic action. Methods Policies relevant to IYCF were identified through web searches and direct approaches to relevant government ministries. Policy content was analysed based on four key domains focussed on mothers, using a qualitative synthesis approach. Three group interviews were conducted using the participatory tool "Net-Map", to identify the influential stakeholders in IYCF policy and programming processes. Results Twenty-six relevant policy documents were analysed for content relating to IYCF. General support for IYCF was found in most of the development plans and high-level health sector policies. Most implementation level documents included support for provision of correct information to mothers. Capacity building of frontline workers for IYCN and system strengthening were well supported through sectoral plans and policies. However, gaps were identified regarding maternity protection, support for monitoring and evaluation, and translation of high-level policy directives into implementation level guidelines, resulting in a lack of clarity over roles and responsibilities. Both government and non-governmental stakeholders, particularly donors, emerged as influential drivers of IYCF policy decisions in Nepal, through technical assistance and funding. The Nutrition Technical Committee under the Ministry of Health, UNICEF, Suaahara, USAID and WHO were identified as key actors providing technical assistance. Key funding agencies were identified as UNICEF and USAID. Conclusions This study reveals strong policy support for key dimensions of IYCF, supported by a highly networked stakeholder environment. Opportunities to further strengthen IYCF policy in Nepal include: further support for training of frontline workers and complementary feeding interventions; extending maternity leave provisions; and clarifying roles and responsibilities of actors, particularly non-governmental actors. Engaging technical and funding agencies and developing partnerships with other relevant actors will be crucial for ensuring effective policy translates into effective practice.